Damping dependence of the reversal time of the magnetization of single-domain ferromagnetic particles for the Neel-Brown model: Langevin dynamics simulations versus analytic results - COFFEY, WILLIAM THOMAS (American Physical Society, 2010)
The damping dependence of the thermally activated reversal time of the magnetization of noninteracting uniaxial single-domain ferromagnetic particles is determined using Langevin dynamics simulations and the analytic Neel-Brown theory with the latter given both in the form of the exact matrix-continued fraction solution of the governing Fokker-Planck equation and its accompanying asymptotes for the escape rate. The reversal time from Langevin dynamics simulations is extremely sensitive to the initial and switching conditions used. Thus if the latter are chosen inappropriately the simulation result may markedly disagree with the analytic one particularly for low damping, where the precessional effects dominate, so that complete agreement can only be obtained by correctly choosing these conditions.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; damping dependence; ferromagnetic particles